Political Dynasties and Regional Governance in Indonesia: Challenges for Democratic Accountability - Susi Sugiyarsih (International Journal of Science Education and Cultural Studies, 2025)
Political dynasties continue to be a recurring problem in Indonesia’s democratic development, especially after the implementation of decentralization and direct local elections. The existence of political families in strategic posts in regional governments continues to attract public attention and raises questions of political competition, democratic accountability and the quality of regional governance. Political dynasties are not illegal, but they often become a subject of controversy over equal political opportunities and concentration of political power. Political dynasties, however, are not just about the passing of political influence from one generation to the next but also about bigger issues of democratic governance and public accountability. In some cases, political power has become concentrated in certain families, and this has raised concerns about political competition, institutional oversight and public participation in local government. However, the impact of political dynasties cannot be looked at uniformly as local political and social conditions differ in different regions. This paper investigates the linkages between political dynasties and regional governance in Indonesia by conducting a review of a variety of academic publications, policy documents, government reports and related literature. The discussion here is on the potential effects of political dynasties on democratic accountability, governance practices and performance of local institutions. Particular emphasis is placed on the difficulties faced by regional governments in promoting transparency, accountability and public trust in democratic processes. The paper argues that in the pursuit of good regional governance, democratic institutions, accountability mechanisms and broader political participation are still needed to be improved so that the political leadership acts in the interest of the public and supports sustainable regional development.